Combined endovascular interventions for pulmonary embolism at high altitude in Tibet - Yang, Tengyan; Yang, Jian (Frontiers in Cardiovascular Medicine, 2024)
Background: Managing pulmonary embolism (PE) at extremely high altitudes poses unique challenges due to harsh environmental conditions and limited healthcare resources. Method: This study retrospectively analyzed Tibetan PE patients in the Tibet Autonomous Region of China to evaluate the effectiveness and safety of combined endovascular interventional therapy in high-altitude areas. Results: The average altitude of long-term residence for Tibetan patients was 3863.4 ± 317.4 m, with an average age of 62.0 ± 16.0 years, and the time from computed tomography pulmonary angiography (CTPA) diagnosis to interventional treatment averaged 2.8 ± 2.2 days. The operation time for these patients was 106.1 ± 22.2 minutes, and the intraoperative dose of alteplase used was 23.3 ± 5.0 mg. All 9 patients reported profound remission of dyspnea and chest pain after endovascular interventions. The heart rate (p＜0.05) and respiratory rate (p＜0.001) of all enrolled patients were significantly decreased, and the peripheral capillary oxygen saturation (SpO2) was significantly increased (p＜0.05) after interventions. No severe complications, such as bleeding, occurred in any patient. Conclusion: This study demonstrated the potential clinical benefits and feasibility of combined endovascular interventional therapy for treating acute PE in extreme high-altitude regions.